Analysis of Social Character Values of Politeness in Nussa and Rara Films - Kurniawati, Kurniawati; Wahyuningsih, Yona; Rachmania, Setyaningsih; Furnamasari, Yayang Furi (Journal of Islamic Communication and Counseling, 2022)
Education is an important aspect of human life since it lasts throughout human life. The politeness value must be instilled from an early age in the family, community, and school environment. The phenomenon of the crisis in the value of politeness is a problem that must be resolved. Character education material contained in the National Education Curriculum, especially regarding the value of politeness, should be conveyed through interactive media to facilitate children's learning and understanding, and one of which is through cartoon/animation films. Accordingly, the above reason is the background for research on the Social Character Analysis of Politeness Value in the Nussa and Rara Films. The purpose of this study, in general, is to analyze the politeness values in the animated series Nussa and Rara and their benefits for cultivating the values of politeness in children. The method in this research was through content analysis by discussing in-depth sentences and scenes in animated films in the form of words, sentences, pictures, cut scenes, paragraphs, and so on. There were ten aspects of politeness character based on the analysis of Nussa and Rara, such as (1) Respect for older people; (2) Receiving something always with the right hand; (3) Do not speak dirty and harsh words; (4) Not being arrogant; (5) Dress modestly; (6) Not spitting carelessly;( 7) Appreciating the efforts of others; (8) Respect the opinions of others; (9) Giving, and (10) Do not interrupt in conversation.